Analisis Sistem dan Prosedur Akuntansi Pengelolaan Dana Desa dalam Meningkatkan Kinerja Pemerintahan Desa (Studi Kasus di Desa Munerana Kecamatan Hewokloang) - Elvin, Alvina; Sanga, Konstantinus Pati; Da Silva, Petrus (Jurnal Projemen UNIPA, 2025)
This Study aimed to Analisys the accounting system and Procedures for village fund management and their impact on improving village government performance. Village fund, sourced from the National Budget (APBN), play a crucial role in rural development and community empowerment. An effective and transparent accounting system is essential to ensure accountibility and efficiency in utilising these funds. This research employed a qualitative upproach, using a case study method, conducted in Munerana Village, Hewokloang Sub- District. The Analysis covered the stages of planning, implementation, administration, reporting, and accountability in village fund management. The findings indicated that the accounting system and procedures in Munerana Village complied with the Minister Of Home Affairs Regulation No. 20 of 2018. However, challenges such as limited community participation and resource constraints must be addressed to enhance service effectiveness. Strengthening the capacity of village officials and enhancing village information system are critical steps toward achieving better and more ustainable village government performance.